Assessment of urban development and land use changes' impact on the environment: a case study of urban development in Klang Valley Region, Malaysia - Yaakup, Ahris (2000)
The increasing demand for housing, employment opportunities, institutions and other urban facilities and services due to migration of rural and town’s dwellers to urban centres leading to drastic changes of urban land covers is believed to be the main factor contributing to the degradation of environmental qualities, namely the increase in temperature, geohazard occurrences, as well as noise, air and water pollution in urban areas. Analyses using various GIS functions were carried out to illustrate the relationship between urban development as well as land use changes and the degradation of environmental qualities in Klang Valley Region. This paper will look into the impact imposed by urban development and land use change upon the trend of environmental quality described earlier.